2021
DOI: 10.3390/ijerph18031224
|View full text |Cite
|
Sign up to set email alerts
|

The Development Strategy of Home-Based Exercise in China Based on the SWOT-AHP Model

Abstract: In view of the increasing importance of sports to people and the impact of COVID-19 on people’s lives, home-based exercise has become a popular choice for people to keep fit due to its unique advantages and its popularity is expected to keep growing in the future. Therefore, it is necessary to determine the development direction of home-based exercise and put in the corresponding efforts. However, there is currently a lack of research on all aspects of home-based exercise. The purpose of this research was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…This was supported by the home-based exercise program proposed by the Government of China, which only included one item related to speed-agility training ( 29 ). In addition, the available space for home-based exercise is very limited which reduces the training options for enhancing speed-agility ( 31 ). Therefore, the growth rate of the speed-agility function decreased during the COVID-19 school closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was supported by the home-based exercise program proposed by the Government of China, which only included one item related to speed-agility training ( 29 ). In addition, the available space for home-based exercise is very limited which reduces the training options for enhancing speed-agility ( 31 ). Therefore, the growth rate of the speed-agility function decreased during the COVID-19 school closure.…”
Section: Discussionmentioning
confidence: 99%
“…This may not always be possible due to the limited space available at home. Thus, it was not easy for the children to perform the balancing exercise that requires large space and specific equipment such as a balance beam ( 31 ). The previous study also found that adolescent football players need to focus on balance training to prevent injury in the restart period after the COVID-19 pandemic because home-based training during the COVID-19 pandemic was insufficient for the football players ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…SWOT matrix is a matching matrix for the company's internal and external strategic factors [29] so that a strategy is obtained that allows the company to be carried out based on the development of four strategies, namely aggressive, conservative, defensive, and competitive [31]. SWOT consists of Strengths, Weaknesses, Opportunities, and Threats [32,33]. Strengths and weaknesses are known as internal factors, and opportunities and threats are external factors [34].…”
Section: Methodsmentioning
confidence: 99%
“…However, considering that each of the selected criteria has a different weight for the purpose of preparing land suitability maps, it would be better to weigh them individually by using the AHP method. The main benefits of the AHP are its capability for checking and reducing the inconsistency of judgments by experts, simplicity and flexibility, applicability for qualitative information and so on 24,25 …”
Section: Introductionmentioning
confidence: 99%
“…The main benefits of the AHP are its capability for checking and reducing the inconsistency of judgments by experts, simplicity and flexibility, applicability for qualitative information and so on. 24,25 Due to the advantages and abilities of the multi-criteria decision analysis and the fuzzy-AHP approaches for planning the use of different lands and evaluation of the development of soil quality indices, 26,27 the aims of this study are to determine suitable locations for ruby vine cultivation using fuzzy-AHP methods. Also, the time of harvest and export of this fruit in other parts of the study area is determined using the growing degree-days (GDD) maps.…”
Section: Introductionmentioning
confidence: 99%